Analisis Pedagogical Content Knowledge Guru: Faktor Pengaruh PCK Guru PPKn Materi Bhinneka Tunggal Ika - Raya, Aqshal Arlian; Hartanto, Rima Vien Permata; Rusnaini, Rusnaini (Academy of Education Journal, 2024)
This research aims to analyze the factors that influence the pedagogical content knowledge of Pancasila and Citizenship Education teachers of SMA Negeri 5 Metro on the material of Bhinneka Tunggal Ika. This research uses a qualitative method by using Shulman's theory which consists of 5 factors: 1) teaching experience; 2) training; 3) learning facilities and infrastructure; 4) teacher self-efficacy; 5) teacher self-motivation. The objects in this study were 2 grade XII Civics teachers. Data analysis used in this study is based on the results of observation sheets, interviews, and documentation studies. The results concluded that the factors that influence teachers' pedagogical content knowledge are 1) teaching experience; 2) training; 3) learning facilities and infrastructure. The other additional finding factors are 1) educational background; 2) ownership of certain positions in the school organization.